Structural Maintenance of Chromosomes 5/6 Complex Is Necessary for Tetraploid Genome Stability in Arabidopsis thaliana - Yang, Fen; Fernández Jiménez, Nadia; Majka, Joanna; Pradillo, Mónica; Pecinka, Ales (Frontiers in Plant Science, 2021)
Polyploidization is a common phenomenon in the evolution of flowering plants. However, only a few genes controlling polyploid genome stability, fitness, and reproductive success are known. Here, we studied the effects of loss-of-function mutations in NSE2 and NSE4A subunits of the Structural Maintenance of Chromosomes 5/6 (SMC5/6) complex in autotetraploid Arabidopsis thaliana plants. The diploid nse2 and nse4a plants show partially reduced fertility and produce about 10% triploid offspring with two paternal and one maternal genome copies. In contrast, the autotetraploid nse2 and nse4a plants were almost sterile and produced hexaploid and aneuploid progeny with the extra genome copies or chromosomes coming from both parents. In addition, tetraploid mutants had more severe meiotic defects, possibly due to the presence of four homologous chromosomes instead of two. Overall, our study suggests that the SMC5/6 complex is an important player in the maintenance of tetraploid genome stability and that autotetraploid Arabidopsis plants have a generally higher frequency of but also higher tolerance for aneuploidy compared to diploids.